Enalapril and endothelial function in arterial hypertension patients of various age - L. I. Katelnitskaya; L. A. Khaisheva; S. A. Pleskachev (Российский кардиологический журнал, 2005)
Vasoactive endothelial function (EF) was assessed in 48 patients with arterial hypertension (AH) (18 participants under 60 years, 30 patients older than 60). Enalapril ("Enam", Dr Reddy's, India) effects on EFwere studied. AH patients were characterized by impaired vasoactive EF, correlating with age. In older patients, endothelial reaction to nitroglycerin was also disturbed. Three-month "Enam" therapy was associated with EF normalization. In blood pressure-normalizing doses, "Enam "facilitated improvement of initially impaired endothelial cells' sensitivity to shear stress.